2012
DOI: 10.1200/jco.2012.30.4_suppl.274
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter retrospective analysis of systemic chemotherapy in poorly differentiated neuroendocrine carcinoma of the digestive system.

Abstract: 274 Background: Poorly differentiated neuroendocrine carcinoma (PDNEC) is a rare and aggressive disease. No standard regimen has yet been established for advanced PDNEC, although regimens for small-cell lung carcinoma such as irinotecan + cisplatin (IP) or etoposide + cisplatin (EP), are usually adopted. The aim of this study was to investigate the outcomes according to the patient’s characteristics and treatment regimens for patients with PDNEC of the digestive system. Methods: Data was collected from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In regard to EP therapy, Moertel et al reported a response rate of 67%, a response duration of 8 months, and a median survival time of 19 months , while Mitry et al reported a response rate of 41.5% and a median survival time of 17.6 months ; according to major reports published to date, the response rate ranges from 14% to 67% and the median survival time ranges from 5.8 to 19 months (Table ). In regard to IP therapy, the response rate has been reported to range from 7% to 60% and the median survival time from 10 to 14 months (Table ). All of these reports, nevertheless, are from small‐scale retrospective studies conducted in patients with NEC including gastrointestinal NEC and P‐NEC, and there has been no report of prospective studies carried out on a sufficient number of patients with P‐NEC alone.…”
Section: Treatment Strategy For P‐necmentioning
confidence: 99%
See 2 more Smart Citations
“…In regard to EP therapy, Moertel et al reported a response rate of 67%, a response duration of 8 months, and a median survival time of 19 months , while Mitry et al reported a response rate of 41.5% and a median survival time of 17.6 months ; according to major reports published to date, the response rate ranges from 14% to 67% and the median survival time ranges from 5.8 to 19 months (Table ). In regard to IP therapy, the response rate has been reported to range from 7% to 60% and the median survival time from 10 to 14 months (Table ). All of these reports, nevertheless, are from small‐scale retrospective studies conducted in patients with NEC including gastrointestinal NEC and P‐NEC, and there has been no report of prospective studies carried out on a sufficient number of patients with P‐NEC alone.…”
Section: Treatment Strategy For P‐necmentioning
confidence: 99%
“…[15]; according to major reports published to date, the response rate ranges from 14% to 67% and the median survival time ranges from 5.8 to 19 months [5,15,16,19,20] ( Table 2). In regard to IP therapy, the response rate has been reported to range from 7% to 60% and the median survival time from 10 to 14 months [20][21][22][23][24][25] (Table 3). All of these reports, nevertheless, are from small-scale retrospective studies conducted in patients with NEC including gastrointestinal NEC and P-NEC, and there has been no report of prospective studies carried out on a sufficient number of patients with P-NEC alone.…”
Section: First-line Chemotherapy For P-necmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012 ASCO, a multicenter retrospective study was reported. For 206 GEP-NEC patients treated with IP/EP, the RR were 50%/27%, the PFS were 5.2/4.0 months, and mOS were 13.0/7.3 months [15]. Similar with GEP-NEC, 3 cases received platinum-based chemotherapy and achieved long survival (Figure 8).…”
Section: Cytotoxic Chemotherapymentioning
confidence: 98%
“…Yamaguchi et al [59,60] reported that the combination of cisplatin and irinotecan offers a response rate of 51% and a progression-free survival of 5.2 months for neuroendocrine carcinomas of various organs, as well as an overall survival of 7.6 months for colorectal neuroendocrine carcinomas in particular. Hainsworth et al [61] used a more aggressive regimen including paclitaxel, carboplatin, and etoposide and reported a response rate of 53% (complete response rate: 15%) and a median progression-free survival of 7.5 months.…”
Section: Management Of Recurrent or Unresectable Tumorsmentioning
confidence: 99%